2014
DOI: 10.1080/10286020.2014.893512
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and antioxidant activity of a heteropolysaccharide isolated from Hedysarum polybotrys

Abstract: A water-soluble polysaccharide (HPS3aS) with a molecular mass of 1.22 × 10(4) Da was isolated from Hedysarum polybotrys using anion-exchange and gel-permeation chromatography. HPS3aS exhibits a globular-shaped conformation in 0.1 M NaNO3 by size exclusion chromatography with multi-angle laser light scattering (SEC-MALLS). The investigation of the structural features of this heteropolysaccharide through a combination of chemical and instrumental analyses revealed that the backbone of HPS3aS is composed of α-D-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…33,34 The signals at 1154.3, 1079.6, and 1025.2 cm À1 indicate that PLB-1-1 has a pyranose structure. [35][36][37] Similarly, in Fig. 3B, it is observed that PLB-1-2 has a strong hydroxyl stretching vibration peak at 3390.4 cm À1 , a methylene hydrocarbon stretching vibration peak at 2928.6 cm, a hydroxyl bending vibration absorption peak at 1642.3 cm À1 , and a methylene hydrocarbon bending stretching vibration peak at 1384.5 cm À1 , which are the representative peaks of a polysaccharide structure.…”
Section: Ft-ir Spectrum Analysis and The Composition Of Monosaccharide For Plb-1-1 And Plb-1-2mentioning
confidence: 53%
See 2 more Smart Citations
“…33,34 The signals at 1154.3, 1079.6, and 1025.2 cm À1 indicate that PLB-1-1 has a pyranose structure. [35][36][37] Similarly, in Fig. 3B, it is observed that PLB-1-2 has a strong hydroxyl stretching vibration peak at 3390.4 cm À1 , a methylene hydrocarbon stretching vibration peak at 2928.6 cm, a hydroxyl bending vibration absorption peak at 1642.3 cm À1 , and a methylene hydrocarbon bending stretching vibration peak at 1384.5 cm À1 , which are the representative peaks of a polysaccharide structure.…”
Section: Ft-ir Spectrum Analysis and The Composition Of Monosaccharide For Plb-1-1 And Plb-1-2mentioning
confidence: 53%
“…GC-MS data indicated that PLB-1-1 contained →4)- d -Glc p -(1→, d -Glc p -(1→, →6)- d -Gal p -(1→, →3)- l -Ara f -(1→, →3,6)- d -Man p -(1→ and →4,6)- d -Man p -(1→ composition. 38,39 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Эпигаллокатехин-галлат зеленого чая обладает иммуномодулирующими свойствами посредством регуляции PI3K/AKT сигнального пути [14]. Гетерополисахариды красного корня обладают антиоксидантными свойствами -связывают 1,1-дифенил-2-пикрилгидразил-, гидроксил-и супероксидрадикалы [40], а также иммуномодулирующими свойствами [39]. Арабиногалактан, полисахарид из древесины лиственницы сибирской, усиливает иммунный ответ благодаря способности стимулировать активность естественных киллеров, макрофагов и секреции провоспалительных цитокинов [17].…”
Section: Discussionunclassified
“…The proliferation of splenocytes and LPS-activated RAW 264.7 cells were stimulated and NO radical scavengering was increased, whereas NO-induced cytotoxicity was decreased. Conversely, the extract also inhibited PGE2, COX-2, iNOS, NO, LPS-activated 264.7 cells, and splenocytes ( 194 ). This finding suggested that the extract can be used when immunity stimulation and anti-inflammatory therapy is required ( 195 ).…”
Section: Medicinal Plants Exhibiting Immunomodulation Activitymentioning
confidence: 99%